A novel Zap70 mutation with reduced protein stability demonstrates the rate‐limiting threshold for Zap70 in T‐cell receptor signalling. Issue 3 (March 2014) - Cauwe, Bénédicte; Tian, Lei; Franckaert, Dean; Pierson, Wim; Staats, Kim A.; Schlenner, Susan M.; Liston, Adrian
Summary Loss of ζ‐associated protein 70 (Zap70) results in severe immunodeficiency in humans and mice because of the critical role of Zap70 in T‐cell receptor (TCR) signalling. Here we describe a novel mouse strain generated by N‐ethyl‐N‐nitrosourea mutagenesis, with the reduced protein stability (rps) mutation in Zap70. The A243V rps mutation resulted in decreased Zap70 protein and a reduced duration of TCR‐induced calcium responses, equivalent to that induced by a 50% decrease in catalytically active Zap70. The reduction of signalling through Zap70 was insufficient to substantially perturb thymic differentiation of conventional CD4 and CD8 T cells, although Foxp3+ regulatory T cells demonstrated altered thymic production and peripheral homeostasis. Despite the mild phenotype, the Zap70A243V variant lies just above the functional threshold for TCR signalling competence, as T cells relying on only a single copy of the Zap70rps allele for TCR signalling demonstrated no intracellular calcium response to TCR stimulation. This addition to the Zap70 allelic series indicates that a rate‐limiting threshold for Zap70 protein levels exists at which signalling capacity switches from nearly intact to effectively null.